Acta Colombiana de Psicología : un importante aporte a la acreditación de alta calidad recientemente obtenida. - Vargas Ordóñez, Carlos (Acta Colombiana de Psicología, 2006)
Un importante aporte a la acreditación de alta calidad recientemente obtenida.